Analisis motivasi belajar pada mata pelajaran IPS kelas IV sekolah dasar - Hesti Hesti; Siti Istiyati; Siti Kamsiyati (Didaktika Dwija Indria, 2023)
This study aims to describe learning motivation in social studies subjects for fourth grade students at SD Negeri Mangkubumen Kidul Surakarta for the academic 2021/2022. This research is qualitative descriptive study. The subjects of this study were students of class IV B SD Negeri Mangkubumen Kidul Surakarta as many as six children, six parents of students, and class IV teachers. Data were obtained from research subjects using observation, interviews, and questionnaires. The validity of the data in this study using source triangulation and technique triangulation. Data analysis used the Miles-Huberman interactive analysis model. The result of this study indicates that the learning motivation of students is included in the category of very high learning motivation. Based on the result of the research, the percentage value of respondent 1 is 98%, respondent 2 is 76%, respondent 3 is 93%, respondent 4 is 73%, respondent 5 is 90%, and the percentage of respondent 6 is 83%. The average percentage value of the six respondents is 86%, the level of learning motivation is classified as very high. It can be concluded that the fourth grade students of SD Negeri Mangkubumen Kidul have a very high level of motivation.